If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7d + -1(6 + -2d) = -6 7d + (6 * -1 + -2d * -1) = -6 7d + (-6 + 2d) = -6 Reorder the terms: -6 + 7d + 2d = -6 Combine like terms: 7d + 2d = 9d -6 + 9d = -6 Add '6' to each side of the equation. -6 + 6 + 9d = -6 + 6 Combine like terms: -6 + 6 = 0 0 + 9d = -6 + 6 9d = -6 + 6 Combine like terms: -6 + 6 = 0 9d = 0 Solving 9d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Divide each side by '9'. d = 0 Simplifying d = 0
| 4(a^3)-2(a^2)-7a-10=0 | | (x-4)(x-2)+1=0 | | 8-9x=17-16x | | 3x-0.5y=0 | | 5a*3b*2a= | | 5d*3e= | | 7a*2a= | | 4+16p+16p^2-36p=0 | | 10b+2=152-5b | | 9x+4y+6z-4x+5z-8y= | | 3k-3=12 | | 13y-3=8y+42 | | 3q=38 | | 125+20= | | 2x^2-x-25=0 | | 128=8t-8 | | 2(3x)=-18 | | 3n-11=22 | | -23p+23=23 | | 5x^2-34x-5=0 | | 8x+13=149 | | 48x^2+84x-432=0 | | 7-2x-(1-3x)/7=2-(2x-1)/3 | | 17x^2+14x-8=0 | | 13x^2-118x+240=0 | | 1-4(-1)(-k/4)=0 | | -5x-3y=13 | | 1-4(-4)(-k/4)=0 | | 4x^2-4bx-(a^2-b^2)=0 | | 4x-3x-2=9 | | a^2x^2-3abx+2b^2=0 | | 22x^3-2162x^2+0.4611x=0 |